A new tetragonal structure type for Li2B2C. Issue 1 (18th December 2014) - Pavlyuk, Volodymyr; Milashys, Viktoriya; Dmytriv, Grygoriy; Ehrenberg, Helmut
<x xml:space="preserve">Abstract</x> The ternary dilithium diboron carbide, Li2B2C (tetragonal, space group P<inline-graphic xlink:href="ark:/27927/pgh31pt6wp4" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />m2, tP10), crystallizes as a new structure type and consists of structural fragments which are typical for structures of elemental lithium and boron or binary borocarbide B13C2. The symmetries of the occupied sites are .m. and 2mm. for the B and C atoms, and <inline-graphic xlink:href="ark:/27927/pgh31pt6wp4" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />m2 and 2mm. for the Li atoms. The coordination polyhedra around the Li atoms are cuboctahedra and 15‐vertex distorted pseudo‐Frank–Kasper polyhedra. The environment of the B atom is a ten‐vertex polyhedron. The nearest neighbours of the C atom are two B atoms, and this group is surrounded by a deformed cuboctahedron with one centred lateral facet. Electronic structure calculations using the TB–LMTO–ASA method reveal strong B...C and B...B interactions.